2018
DOI: 10.1039/c7ra13491f
|View full text |Cite
|
Sign up to set email alerts
|

Green synthesis of a Cu/MgO nanocomposite by Cassytha filiformis L. extract and investigation of its catalytic activity in the reduction of methylene blue, congo red and nitro compounds in aqueous media

Abstract: This work reports the green synthesis of a Cu/MgO nanocomposite using Cassytha filiformis L. extract as a reducing agent without stabilizers or surfactants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 120 publications
(26 citation statements)
references
References 42 publications
0
26
0
Order By: Relevance
“…Interestingly, some compounds identified in the methanolic extract of S. didymobotrya roots in this study have a potential to take part in the formation of nanoparticles. For instance, alizarin (a dihydroxyanthraquinone with two hydroxyl groups on a phenyl ring) possesses a structure similar to compounds proposed to take part in chelation and reduction of copper ions to CuNPs [2,56].…”
Section: Gc-ms Resultsmentioning
confidence: 99%
“…Interestingly, some compounds identified in the methanolic extract of S. didymobotrya roots in this study have a potential to take part in the formation of nanoparticles. For instance, alizarin (a dihydroxyanthraquinone with two hydroxyl groups on a phenyl ring) possesses a structure similar to compounds proposed to take part in chelation and reduction of copper ions to CuNPs [2,56].…”
Section: Gc-ms Resultsmentioning
confidence: 99%
“…Most recently, Nasrollahzadeh and co‐workers have produced Cu/MgO nanocomposite using Cassytha filiformis L. extract (Figure ) . Reduction and stabilization of Cu NPs were ascribed to the flavonoids present in the extract.…”
Section: Oxidation Of Benzyl Alcohol and Reduction/degradation Of Nitmentioning
confidence: 99%
“…In recent years, various researchers especially a research group at nanobiotechnology Laboratory, University of Qom, Iran have reported their efforts to rationalize the mechanism while synthesizing Cu and CuO nanoparticles from various plants such as Ginkgo biloba L ., Euphorbia esula L., Otostegia persica , Plantago asiatica , Euphorbia bungei Boiss , Thymus vulgaris L., Theobroma cacao L., barberry fruit, Gundelia tournefortii , Anthemis xylopoda flowers, Euphorbia prolifera , Orchis mascula L., Silybum marianum L., Melissa Officinalis L., Cassytha filiformis L., Centella asiatica L., Anthemis nobilis , Morinda morindoides . They reported that the antioxidant flavonoids, polyphenols and phenolic acids of the plant extract contribute to the reduction of Cu ions to Cu NPs (Figure ) as OH functional groups in their structure were oxidized to carbonyl groups .…”
Section: Probable Mechanisms For Green Synthesis Of Mnps Using Plant mentioning
confidence: 99%
“…Due to that, nanomaterials were introduced in order to mitigate this problem as these materials have unique properties to be explored. Since then, an extensive amount of studies had been done during the last decade and it also has been widely expand to be utilized into multidiscipline applications [5][6][7]. Nanocomposite is one of the classifications in nanomaterials where it could be defined as a materials that have at least one of them in a dimension of less than 100 nm scale [8].…”
Section: Introductionmentioning
confidence: 99%